Tujuan Pemidanaan dalam Hukum Pidana Nasional dan Fiqh Jinayah - nafi' mubarok (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2015)
Abstract: Crime is a pattern of behavior that is detrimental to ‎society and causing victims, that will cause a social reaction. ‎One form of social reaction is penal policy, which is a ‎strategy to resolve crime by the use of criminal law. In penal ‎policy is necessary to formulate a background or reasons for ‎the use of the criminal law, or commonly known as the ‎formulation of the Purposes of Punishment, which has the ‎function to (1) create a synchronization both physically and ‎culturally; (2) control functions, provide a philosophical ‎foundation, the basis of rationality and motivation of ‎punishment; (3) determine the ultimate purpose of the ‎criminal law, and (4) implementation of the norms of ‎criminal law. This paper focuses on the study of "the purpose ‎of punishment", presented by the systematics of: (1) ‎exposure of the various theories of the purpose of ‎punishment, (2) the purpose of punishment in the National ‎Criminal Law , and (3) the purpose of punishment in fiqh ‎jinayah. As a complement, at the end of this article described ‎the purpose of punishment of the National Criminal Law in ‎the future.‎ Abstrak: Kejahatan merupakan suatu pola tingkah laku yang ‎merugikan masyarakat sehingga menimbulkan korban, yang ‎pada akhirnya melahirkan reaksi sosial. Salah satu bentuk ‎reaksi sosial adalah adanya penal policy, yaitu strategi untuk ‎menanggulangi kejahatan dengan menggunakan sarana hukum ‎pidana. Dalam penal policy inilah perlu dirumusaan latar ‎belakang atau alasan penggunaan pidana tersebut, atau yang ‎biasa disebut dengan perumusan tujuan pemidanaan, yang ‎mempunyai fungsi untuk (1) menciptakan sinkronisasi baik ‎fisik maupun kultural; (2) fungsi kontrol, memberikan ‎landasan filosofis, dasar rasionalitas dan motivasi ‎pemidanaan; (3) mengetahui tujuan akhir dari penggunaan ‎hukum pidana, dan (4) ditaatinya norma pidana. Tulisan ini ‎memfokuskan pada penelaahan/kajian “tujuan pemidanaan, ‎dengan urutan pembahasan (1) pemaparan berbagai teori ‎tujuan pemidanaan, (2) tujuan pemidanaan dalam Hukum ‎Pidana Nasional, dan (3) tujuan pemidanaan dalam fikih ‎jinayah. Sebagai penyempurna, di akhir tulisan ini dipaparkan ‎tujuan pemidanaan dari Hukum Pidana Nasional di masa ‎yang akan datang. ‎